การสร้างบทเรียนแบบโปรแกรมวิชาคณิตศาสตร์เรื่อง "การจัดลำดับและการจัดหมู่" สำหรับระดับมัธยมศึกษาตอนปลาย - ปราโมทย์ เงียบประเสริฐ (จุฬาลงกรณ์มหาวิทยาลัย, 1976)
The purpose of this research was to construct a mathematics programmed lesson on "Permutations and Combinations" at the upper secondary education level and to investigate the effectiveness of the programmed lesson based on the 90/90 standard. The researcher constructed the 193 frames of the programmed lesson and the fifty test items on "Permutations and Combinations". One hundred students were used as the sample group for the experiment. They were given the pre-test before and the post-test after they had studied the programmed lesson. The data was collected and analyzed to find out the effectiveness of the programmed lesson, according to the 90/90 standard. The analysis of the test result indicated that the programmed lesson has met the 90/90 standard at the 96.69/74.84 level. The effectiveness of the programmed lesson was higher than the first 90 standard but less than the second 90. However, the arith¬metic means (X ̅) of the pre-test and the post-test showed statisti¬cally significant differences at the level of .01. Thus, it can be concluded that this programmed lesson has significantly improved the students knowledge of permutations and combinations.